Economic Impact Of Forest Management Institutions On Groundwater Recharge in Karnataka, India - Patil, Vikram; Chandrakanth, M. G.; Gangadharappa, N. R.; Manjunatha, A. V.; Shivanagouda, B. (Indian Forester, 2014)
Present study signifies relative hydrological and economic contribution of Joint Forest Planning and Management (JFPM) programme in semi-arid tropical India towards groundwater recharge. A majority of dugwells / open wells have failed to yield water in hardrock areas of India due to advent of deep borewells, low rainfall and poor recharge. Field data were collected for 2008 from a population of farmers possessing irrigation wells in selected villages with and without JFPM programme. Logarithmic net returns, descriptive statistics and ANOVA reveal that the net returns to land, irrigation water and expenditure for irrigation water increased due to groundwater recharge caused by the JFPM programme. JFPM has contributed towards 100 percent functioning of all borewells and dug wells with no negative externality in JFPM village valued in terms of well failure. Incremental net returns due to JFPM (of ` 13342 per acre) are at least 100 percent higher than that of watershed development Programme, WDP (of ` 6343 per acre) and JFPM + WDP (of ` 6822 per acre). Groundwater yield of dug wells was just 10 percent lower than that of deep borewells, demonstrating potential of JFPM in recharging dug wells. Groundwater cost was 35 per cent lower in JFPM compared with control village, due to groundwater recharge. Net return per rupee of cost of groundwater was the highest for JFPM dug well (` 11.3) followed by JFPM borewell (` 8.42), JFPM + WDP (` 3.26), WDP (` 3.05) and control farmers (` 1.04). JFPM has successfully recharged groundwater in irrigation wells and can be replicated in hard rock areas benefiting scores of farmers at relatively low cost.